Transformational Leadership and Work‒Life Balance Effects on Job Satisfaction: Organizational Commitment as a Mediator - Ridhani, Aulia; Rahmawati, Rini (Quantitative Economics and Management Studies, 2025)
Employee job satisfaction is a critical determinant of organizational performance, with transformational leadership and work‒life balance emerging as significant factors. However, the literature reveals inconsistent relationships between these variables across different organizational contexts, indicating the need for further investigation into potential mediating variables. This study investigated the impact of transformational leadership and work‒life balance on job satisfaction, with organizational commitment serving as an intervening variable at PTs. PLN (Persero) Marabahan Customer Service Unit. Using a quantitative methodology, data were collected via questionnaires from 58 technical employees selected through purposive sampling. Variables were assessed via Likert scales, and analysis was conducted via structural equation modeling-partial least squares (SEM-PLS) facilitated by Smart PLS-4 software. The findings revealed that both transformational leadership style and work‒life balance positively and significantly influenced job satisfaction among technical personnel. Furthermore, organizational commitment was demonstrated to function effectively as a mediating variable in the relationship between the independent variables (transformational leadership and work-life balance) and the dependent variable (job satisfaction) and to directly enhance employee satisfaction levels. These findings suggest that an inspiring leadership style and a well-balanced work-life environment not only directly improve job satisfaction but also do so through increased organizational commitment, ultimately contributing to employee well-being and productivity.